Using Probability Theory to Identify the Unsure Value of an Incomplete Sentence - Nur Fatin Nabila Mohd Rafei Heng; Nurlida Basir; Madihah Mohd Saudi; Sakinah Ali Pitchay; Farida Hazwani Mohd Ridzuan; Mamat A.; Deris M.M. (Institute of Electrical and Electronics Engineers Inc., 2024)
Indexed by WOS/ Scopus